2018
DOI: 10.1038/s42003-018-0096-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Uranotaenia sapphirina as a specialist of annelids broadens known mosquito host use patterns

Abstract: Feeding upon vertebrate blood by mosquitoes permits transmission of diverse pathogens, including viruses, protozoa, and nematodes. Despite over a century of intensive study, no mosquito species is known to specialize on non-vertebrate hosts. Using molecular analyses and field observations, we provide the first evidence, to our knowledge, that a mosquito, Uranotaenia sapphirina, specializes on annelid hosts (earthworms and leeches) while its sympatric congener, Uranotaenia lowii, feeds only on anurans (frogs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 81 publications
(89 reference statements)
5
53
0
3
Order By: Relevance
“…vexans feeds on people and other mammals, especially deer, cattle, horses, rabbits, sheep, and dogs [8]. U. sapphirina is found in the eastern, central and southern US, and is the only mosquito known to feed on invertebrates, mainly earthworms and leeches [9]. Our finding that this species was infected with R. felis is of note as leeches have previously been suggested to be vectors of the organism [10].…”
mentioning
confidence: 66%
“…vexans feeds on people and other mammals, especially deer, cattle, horses, rabbits, sheep, and dogs [8]. U. sapphirina is found in the eastern, central and southern US, and is the only mosquito known to feed on invertebrates, mainly earthworms and leeches [9]. Our finding that this species was infected with R. felis is of note as leeches have previously been suggested to be vectors of the organism [10].…”
mentioning
confidence: 66%
“…However, variation in the efficiency of amplification between host taxa may pose an issue, and further research is needed to investigate the suitability of these, or other primers to next generation and community sequencing blood meal analysis approaches. Future research should also consider the possibility that some mosquitoes are specialists of non-vertebrate hosts [ 59 ], and strive to develop blood meal analysis methods that can detect the full range of animals that may be fed upon by mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…uniformis feed on frogs through the year in an opportunistic manner. Similarly, some studies have shown that Uranotaenia mosquitoes feed on anuran blood (Borkent & Belton, 2006;Toma et al, 2014;Camp et al, 2018;Reeves et al, 2018), but the feeding behaviour of species in this genus had not been documented for the species studied here. Uranotaenia rutherfordi had previously been reported only once in Sri Lanka during a mosquito survey performed in the early 1900s from the same locality, Peradeniya in Kandy District (Barraud, 1934).…”
Section: Discussionmentioning
confidence: 66%
“…Hematophagous insects that specialise in attacking frogs, such as frog-biting midges (Diptera: Corethrellidae McKeever, 1977;Bernal et al, 2006;Borkent, 2008), can use the mating calls of their anuran host and could selectively approach some species of the host over others. In addition to frog-biting midges, some species of mosquitoes from the genus Uranotaenia also primarily feed on anuran hosts (Heatwole & Shine, 1976;Kay et al, 1979;Cupp et al, 2004;Borkent & Belton, 2006;Toma et al, 2014;Camp et al, 2018;Reeves et al, 2018) and have also been recognised to use the mating calls of male anurans to locate them (Borkent & Belton, 2006;Toma et al, 2014;Camp et al, 2018). So far, however, there have been no reports of species-specific associations or host partitioning in flies specialised on anuran hosts (Borkent, 2008;Grafe et al, 2019).…”
Section: Introductionmentioning
confidence: 99%